Raptor abundance and northern bobwhite survival and habitat use. (1st September 2014) - Turner, Joshua W.; Hernández, Fidel; Boal, Clint W.; Ballard, Bart M.; Bryant, Fred C.; Wester, David B.
ABSTRACT Predation risk has a profound influence on prey behavior and habitat use. The Rio Grande Plains ecoregion of Texas, USA, provides a unique opportunity to investigate changes in prey behavior because the ecoregion experiences a high influx of raptors every year during autumn migration. We used an 8‐year data set (2000–2008) of radiocollared northern bobwhites (Colinus virginianus) and raptor abundance to test the hypothesis that bobwhites responded to increased raptor abundance via changes in woody‐cover use at the home‐range scale. Bobwhite survival was negatively correlated with raptor abundance, with red‐tailed hawks (Buteo jamaicensis), and northern harriers (Circus cyaneus) accounting for 51% of the variability in bobwhite survival (P < 0.010). However, we documented no change in the amount of woody cover used by bobwhites in their home range between the raptor migration (6.6% ± 0.5%; n = 73 bobwhites) and non‐migration periods (7.1% ± 0.4%; n = 105 bobwhites; P = 0.490). In addition, bobwhites that survived the raptor migration period used similar amounts of woody cover within their home range (6.3% ± 0.6%, n = 58 bobwhites) compared with those dying during the migration period (6.8% ± 0.4%, n = 100 bobwhites; P = 0.530). Our data suggest that bobwhites do not alter their use of woody cover at the home‐range scale in response to increasing raptor abundance, but this does not preclude increased use of woody cover at the point‐of‐use scale. © 2014 The Wildlife Society.